Synthesis and antimicrobial activities of some (E)-N’-1-(substituted benzylidene)benzohydrazides - Manikandan, V.; Balaji, S.; Senbagam, R.; Vijayakumar, R.; Rajarajan, M.; Vanangamudi, G.; Arulkumaran, R.; Sundararajan, R.; Thirunarayanan, G. (International Journal of Advanced Chemistry, 2017)
About ten substituted (E)-N'-1-(substituted benzylidene) benzohydrazides have been synthesized. They are analyzed by their analytical, ultra violet (UV), Fourier transform-IR (FT-IR) and nuclear magnetic resonance (NMR) spectral data and evaluated by antimicrobial activities such antibacterial and antifungal activities.